Covid-19 and marketing strategies - Hasrul, Nur Izzati; Rashid, Umi Kartini; Harun, Amran (Penerbit UTHM, 2022)
COVID-19 is the disease caused by a new coronavirus, SARS-CoV-2. It was named a coronavirus because the virus represents crown-like spikes on the outer surface of the virus (WHO, 2020). According to the World Health Organization (WHO, 2020), the first case reported was on December 31, 2019. The first case reported was a 'viral pneumonia' cluster at a Seafood Wholesale Market in Wuhan, China. On March 11, 2020, WHO declared the COVID-19 outbreak as a global pandemic. This disease was characterized as a pandemic because of its rapid spread, affecting many people and occurring worldwide. Common symptoms of this disease are high fever, dry cough, and fatigue. Other symptoms can be loss of taste and smell, headache, muscle pain, etc.